2015
DOI: 10.1111/1471-0528.13685
|View full text |Cite
|
Sign up to set email alerts
|

Funnel compression suture: a conservative procedure to control postpartum bleeding from the lower uterine segment

Abstract: Bleeding from the lower uterine segment (LUS) during caesarean section remains a life-threatening obstetric problem, particularly in women with placenta praevia or partial placenta accreta in the LUS. Various conservative measures for the surgical treatment of postpartum haemorrhage have been studied for decades. In this paper we describe a funnel compression suture to staunch intractable bleeding from LUS for placenta praevia accreta. The suture brings the anterior and posterior walls of the LUS together usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 26 publications
0
20
1
Order By: Relevance
“…16,17 Palacios-Jaraquemada et al 18 reported uterine repair among patients with anterior placenta percreta, achieving hemostasis with selective vascular ligature or surgical myometrial compression. 7,19,20 Another conservative management approach involves leaving the placenta in situ; however, this strategy is associated with adverse effects, including delayed hemorrhage and infection. The rate of uterine preservation was 73.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Palacios-Jaraquemada et al 18 reported uterine repair among patients with anterior placenta percreta, achieving hemostasis with selective vascular ligature or surgical myometrial compression. 7,19,20 Another conservative management approach involves leaving the placenta in situ; however, this strategy is associated with adverse effects, including delayed hemorrhage and infection. The rate of uterine preservation was 73.5%.…”
Section: Discussionmentioning
confidence: 99%
“…18 By contrast, the uterine conservation rate in the present study was approximately 94%, higher than the rates reported in other case series (78%-85%). 7,19,20 Another conservative management approach involves leaving the placenta in situ; however, this strategy is associated with adverse effects, including delayed hemorrhage and infection. 20 In particular, delayed hemorrhage was found to require hysterectomy at 3-9 months after cesarean delivery among 22%-58% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Severe complications, such as uterine necrosis and pyometra, were not observed in any group. Different UCS placement methods have been proposed, and various outcomes and associated complications have been reported . To our knowledge, however, no previous studies have compared postoperative complications between women treated with and those not treated with UCSs.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine compression sutures (UCS) are a recent innovation used to address PPH. A variety of UCS, including our series of reports, have achieved good hemostasis and preserved life and fertility. However, postoperative complications related to the remnant thread and persistent squeeze of UCS have been widely described in recent decades …”
Section: Introductionmentioning
confidence: 75%
“…In order to avoid possible adverse effects of our suturing techniques described previously, we devised a new ring compression suture (RCS), or removable uterus‐pubis binding suture (RUPBS), whose threads, that might induce potential adverse effects, are removed after 48 h postoperatively. The procedure is highly effective and can be used as an alternative to peripartum hysterectomy in every case of uncontrollable PPH and also has potential for prophylactic application in PPH.…”
Section: Introductionmentioning
confidence: 99%